Eksistensi Lembaga Pendidikan Dayah dalam Ekskalasi Politik Bangsa - Hadi, Abdul (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2017)
Dayah is a typical Acehnese educational institution that has long played a very important role in maintaining political stability especially in Aceh. This educational institution has spawned many fighters, reformers and politicians both local and national level. This institution has been born since the arrival of Islam to Aceh and still exist until now with the dynamics that continue to grow. The relationship of dayah educational institutions with the authorities has spawned many government policies in order to reduce conflict and enforcement of Islamic law in Aceh. As a form of state responsibility in maintaining the sustainability and existence of dayah educational institutions the government has established a special body equivalent to other education offices in Aceh named Badan Pembinaan Pendidikan Dayah (BPPD) Aceh. Thus, dayah education is recognized as an official educational institution. The alumni of this institution have the same rights as alumni from other formal education institutions in Aceh.